Evidence‐based vegetation management: prospects and challenges. Issue 3 (30th May 2014) - Milberg, Per; Palmer, Michael
Abstract The effect of applied vegetation science on society has the potential to increase by adopting an evidence‐based approach. However, this would require a shift in focus towards effect size and results suitable for meta‐analyses, a focus on practitioners as potential readers, more emphasis on practical problems rather than mechanism, and an acceptance of all well‐executed experimental studies, even if confirmatory. Thus, the prevailing editorial policies need to be reconsidered, as well as the methods of analysing, reporting and evaluating research, for our research efforts to be of better use within society.